Determining the Effect of Intrathecal Dexmedetomidine on Postoperative Pain Relief after Cesarean Section - Ayesha Shahid; Huda Shafqat; Salman Maqbool; Ahsan Ali; Rehana Feroze (Journal of Bahria University Medical and Dental College)
Objective: To analyze efficacy of intrathecal Dexmedetomidine as adjunct to hyperbaric Bupivacaine in terms of postoperative analgesia after caesarean section. Study Design & Setting: This randomized controlled trial was conducted at Department of Anesthesia, Rawal Institute of Health Sciences, Islamabad from20th, October 2018 to 20thApril 2019 after taking Ethical board approval from the Institute. (letter no RIHS-REC/030/18, dated, 18th October 2018). Methodology: Total n=120 patients having ASA status I, II undergoing elective cesarean section were randomly divided into 2groups (60 each) by lottery method. Group-A, was given hyperbaricBupivacaine (0.5%) 12mg alone and group-B, was given hyperbaricBupivacaine (0.5%) 12mg along with injection Dexmedetomidine 4ug in intrathecal space respectively. Patients were followed in postoperative period for onset of pain and requirement for rescue analgesia in first 6 hours. Results: There was statistically significant difference in mean onset of postoperative pain among both the groups-A and B (178.18 ± 12.51 versus 364.07± 35.58min respectively with p value 0.000), as well as, postoperative analgesic requirement, in first 6 hours, 39 (65.0 %) versus 31 (51.7 %) with p-value 0.000 respectively. However, on stratification, considering effect modifiers, like age (20-30 years and 30-40 year and previous history of cesarean section), there was statistically significant difference in mean onset of pain in both groups, but no significant difference was found regarding rescue analgesic requirement in both groups. Conclusion: Intrathecal Dexmedetomidine along with hyperbaric Bupivacaine was better than hyperbaric Bupivacaine alone in controlling postoperative pain in caesarean section.